Peran Corporate Social Responsibility dalam Meningkatkan Kesejahteraan Penyandang Disabilitas (Studi Kasus CSR PT Bio Farma) - Izzadilla Hidayanu Pratiwi; Dewi Rahmi (UNISBA Press, 2024)
Abstract. CSR PT Bio Farma created an empowerment program for people with disabilities as a form of corporate concern to improve welfare, so that they can participate in achieving sustainable development without any parties being left out, including people with disabilities. The purpose of this research is to find out the role of Corporate Social Responsibility in improving the welfare of persons with disabilities. The research method used is descriptive qualitative. This type of research is a case study. The data source used in this research is primary data. The informants in this research are the head of the partnership and environment section of PT Bio Farma and the Group of Persons with Disabilities assisted by PT Bio Farma CSR. The results of this study indicate that there is a positive impact felt by persons with disabilities who participate in the empowerment program for persons with disabilities carried out by CSR PT Bio Farma. The positive impact can be seen from the results of the beneficiaries' statements on the indicators of the welfare of persons with disabilities on a. Increased Skills and Knowledge, b. Access to Employment Opportunities, c. Income, d. Social Support. Social Support. This program has helped people with disabilities in improving the welfare and better quality of life of people with disabilities. Abstrak. CSR PT Bio Farma membuat program pemberdayaan untuk penyandang disabilitas sebagai bentuk kepedulian perusahaan untuk meningkatkan kesejahteraan, sehingga dapat berpartisipasi dalam mencapai pembangunan berkelanjutan tanpa ada pihak yang ditinggalkan termasuk penyandang disabilitas. Tujuan penelitian ini untuk mengetahui bagaimana peran Corporate Social Responsibility dalam meningkatkan kesejahteraan penyandang disabilitas. Metode penelitian yang digunakan adalah deskriptif kualitatif. Jenis penelitian ini yaitu studi kasus. Sumber data yang digunakan dalam penelitian ini yaitu data primer. Informan pada penelitian ini yaitu kepala seksi kemitraan dan lingkungan PT Bio Farma dan Kelompok Penyandang Disabilitas binaan CSR PT Bio Farma. Hasil penelitian ini menunjukkan adanya dampak positif yang dirasakan penyandang disabilitas yang mengikuti program pemberdayaan penyandang disabilitas yang dilakukan CSR PT Bio Farma. Dampak positif terlihat dari hasil pernyataan penerima manfaat terhadap indikator kesejahteraan penyandang disabilitas pada: a. Peningkatan Keterampilan dan Pengetahuan, b. Akses Kesempatan Kerja, c. Pendapatan, d. Dukungan Sosial. Program ini telah membantu penyandang disabilitas dalam meningkatkan kesejahteraan dan kualitas hidup penyandang disabilitas yang lebih baik.